1993
DOI: 10.1093/hmg/2.7.915
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 mutations in aniridia

Abstract: Aniridia is a congenital malformation of the eye, chiefly characterised by iris hypoplasia, which can cause blindness. The PAX6 gene was isolated as a candidate aniridia gene by positional cloning from the smallest region of overlap of aniridia-associated deletions. Subsequently PAX6 intragenic mutations were demonstrated in Smalleye, a mouse mutant which is an animal model for aniridia, and six human aniridia patients. In this paper we describe four additional PAX6 point mutations in aniridia patients, both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 0 publications
2
101
0
2
Order By: Relevance
“…Thus, the C to T substitution leads to disruption of PAX6 expression due to premature termination, causing loss of activity at one allele. 31 Further investigations of PAX6 protein translation and function are required to understand the molecular function that the PAX6 IVS9-12C to T polymorphism plays in ocular development and/or myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the C to T substitution leads to disruption of PAX6 expression due to premature termination, causing loss of activity at one allele. 31 Further investigations of PAX6 protein translation and function are required to understand the molecular function that the PAX6 IVS9-12C to T polymorphism plays in ocular development and/or myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been proposed as a possible candidate gene for the mental retardation phenotype associated with WAGR. The deletion observed in our patient extends telomerically to F1238 (interval XV, Fantes et al, 1995b) and may have also included the BDNF (brain-derived neurotrophic locus), which has also been implicated in the mental retardation phenotype (Hanson et al, 1993;Fantes et al, 1995b). Our patient, however, was not mentally retarded, so detailed mapping of the distal breakpoint may be significant in defining the location of other possible retardation associated gene(s).…”
Section: Discussionmentioning
confidence: 69%
“…DNA studies have shown that the majority of sporadic aniridia is caused by intragenic mutations of PAX6 resulting in haploinsufficiency of the PAX6 gene product (Jordan et al, 1992;Glaser et al, 1992;Hanson et al, 1993;Axton et al, 1997). In very rare cases of balanced structural chromosomal rearrangements with 11p13 breakpoints, the mutant phenotype has probably resulted from a position effect following disruption of the chromatin domain distal to the PAX6 locus.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation is thought to result in decreased P6CON transcriptional activity and in increased 5aCON transcriptional activity. In contrast, in aniridia patients who are haploinsufficient for PAX6, both the anterior and posterior parts are affected generally (Glaser et al 1992;Hanson et al 1993; 13, 1, 3, 10, 30, 100 and 300 ng; lanes 15-20, 100, 300 and 1000 ng) were co-transfected with either P6CON-luc (5 mg, lanes 1-13) or 5aCON-luc (5 mg, lanes 14-20). The mutation reduces transactivation via P6CON, whereas it hyperactivates transcription directed from 5aCON.…”
Section: Phenotype-genotype Correlations Of Pax6 Mutantsmentioning
confidence: 99%